2000
DOI: 10.1038/modpathol.3880238
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Ampulla of Vater Associated With or Without Adenoma: A Clinicopathologic Analysis of 198 Cases With Reference to p53 and Ki-67 Immunohistochemical Expressions

Abstract: Adenomatous areas are found frequently within or in the vicinity of carcinoma of the ampulla of Vater. This makes definite diagnosis difficult in the preoperative examination. The adenoma-carcinoma development hypothesis is generally accepted for colorectal tumors. Recently, a genetic alteration model during colorectal tumor development has attracted much attention, leading to various studies. We studied clinicopathologic features, prognostic factors, and the alteration of the p53 tumor suppressor gene using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 20 publications
3
37
2
5
Order By: Relevance
“…4,5,[29][30][31] In our series, 74% of patients with ampullary carcinomas had evidence of coexisting adenomas which is in line with the literature reporting synchronous lesions in 30-91% of cases. 4,5 Differentiating normal mucosa with reactive atypia from dysplasia or dysplasia from invasive carcinoma can be challenging or even impossible in bioptic material. Markers for ampullary dysplasia or invasive carcinoma could therefore be of great diagnostic value.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…4,5,[29][30][31] In our series, 74% of patients with ampullary carcinomas had evidence of coexisting adenomas which is in line with the literature reporting synchronous lesions in 30-91% of cases. 4,5 Differentiating normal mucosa with reactive atypia from dysplasia or dysplasia from invasive carcinoma can be challenging or even impossible in bioptic material. Markers for ampullary dysplasia or invasive carcinoma could therefore be of great diagnostic value.…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3] In up to 91% of cases, residual adenomas can be detected in the tumor periphery, indicating an adenoma-carcinoma sequence similar to that observed in colorectal cancer. 4,5 Patients commonly present early with obstructive jaundice due to neoplastic occlusion of the ampullary orifice. 6 Early detection but also biologic differences are held responsible for the better prognosis of ampullary tumors following pancreaticoduodenectomy compared with other periampullary tumors (median survival 30-50 months, 5-year survival rate 21-64%).…”
mentioning
confidence: 99%
“…Adenoma lesion is often seen around carcinoma lesion [242][243][244] and the abnormal findings of oncogene and tumor suppressor gene in adenoma are also reported [244,245].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that SIT induces a shift from a TH2-cell cytokine secretion profile, interleukin (IL)-4, IL-5 and IL-13, with secondary IgE production to a TH1-cell type, interferon (IFN)-γ [12,13,14,15], although there is conflicting evidence on the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%